2006
DOI: 10.1016/j.visres.2005.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Irrepressible saccades from a tectal lesion in a Rhesus monkey

Abstract: We present a case of spontaneously occurring irrepressible saccades in an experimental Rhesus monkey. Though eye jerks are sometimes associated with cerebellar disease, central demyelination or brainstem lesions, there is little consensus on their neurological mechanisms. From neurological and anatomical investigation we report that these irrepressible saccades were caused by a discrete cerebrovascular accident that involved the rostral superior colliculus along with its commissure, and with minor invasion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 35 publications
4
10
0
Order By: Relevance
“…Irrepressible saccades were reported to have been observed in a rhesus monkey caused by a stroke that involved the rostral superior colliculus along with its commissure and with minor invasion of the periaquaductal gray and adjacent mesencephalic reticular formation [13]. This was consistent with the results from a physiological study on a monkey [29] where a subset of neurons in the rostral pole of the superior colliculus, when subjected to inhibition using a pharmacological GABA agonist, caused unwanted saccadic eye movements.…”
Section: Discussionsupporting
confidence: 84%
“…Irrepressible saccades were reported to have been observed in a rhesus monkey caused by a stroke that involved the rostral superior colliculus along with its commissure and with minor invasion of the periaquaductal gray and adjacent mesencephalic reticular formation [13]. This was consistent with the results from a physiological study on a monkey [29] where a subset of neurons in the rostral pole of the superior colliculus, when subjected to inhibition using a pharmacological GABA agonist, caused unwanted saccadic eye movements.…”
Section: Discussionsupporting
confidence: 84%
“…In PSP, covert orienting has been found to be delayed in directions in which eye movements are most affected, suggesting a role for midbrain pathways, including the SC [33]. SC lesion studies in humans and non-human primates have demonstrated abnormal saccade and disruption of reflexive eye movements [4, 36]. For the IC, tau pathology in AD did not become significant until Braak V, suggesting this nucleus is affected later in the disease, when a patient already has severe impairments, rendering clinicopathologic correlates problematic.…”
Section: Discussionmentioning
confidence: 99%
“…No irrepressible saccades occurred, however, suggesting that the lesion spared the fixation neurons located in the anterior superior colliculus. Indeed, irrepressible saccades did occur in an experimental monkey in whom the lesion encroached upon the anterior superior colliculus part and the collicular commissure [37].…”
Section: Control Of Saccade Initiation and Saccadic Intrusionsmentioning
confidence: 98%